The impact of affective temperaments on clinical and functional outcome of Bipolar I patients that initiated or changed pharmacological treatment for mania. (March 2018) - Perugi, G.; Cesari, D.; Vannucchi, G.; Maccariello, G.; Barbuti, M.; De Bartolomeis, A.; Fagiolini, A.; Maina, G.
Abstract: Background: Affective temperaments have been shown to impact on the clinical manifestations and the course of bipolar disorder. We investigated their influence on clinical features and functional outcome of manic episode. Method: In a naturalistic, multicenter, national study, a sample of 194 BD I patients that initated or changed pharmacological treatment for DSM-IV-TR manic episode underwent a comprehensive evaluation including briefTEMPS-M, CTQ, YMRS, MADRS, FAST, and CGI-BP. Factorial, correlation and comparative analyses were conducted on different temperamental subtypes. Results: Depressive, cyclothymic, irritable and anxious temperaments resulted significantly correlated with each other. On the contrary, hyperthymic temperament scores were not correlated with the other temperamental dimensions. The factorial analysis of the briefTEMPS-M sub-scales total scores allowed the extraction of two factors: the Cyclothymic-Depressive-Anxious (Cyclo-Dep-Anx) and the Hyperthymic. At final evaluation Dominant Cyclo-Dep-Anx patients reported higer scores in MADRS and in CTQ emotional neglect and abuse subscale scores than Dominant Hyperthymic patients. The latter showed a greater functional outcome than Cyclo-Dep-Anx patients. Conclusions: Affective temperaments seem to influence the course of mania. Childhood emotional abuse and neglect were related to the cyclothymic disposition. Cyclothymic subjects showed more residual depressive symptoms and Hyperthymic temperament is associated with a better short-term functional outcome. Highlights: Affective temperaments impact on the clinical and functional outcome of mania. Childhood emotional abuse and neglect were related to the cyclothymic disposition. Dominant Cyclothymic subjects showed more residual depressive symptoms. Dominant Hyperthymic patients showed a better functional outcome.